Treatment response in relation to subthreshold bipolarity in patients with major depressive disorder receiving antidepressant monotherapy: a post hoc data analysis (KOMDD study) - Park Y; Lee B (Neuropsychiatric Disease and Treatment, 2016)
Young-Min Park,1 Bun-Hee Lee2 1Department of Psychiatry, Ilsan Paik Hospital, Inje University College of Medicine, Goyang, 2Department of Psychiatry, Seoul Eunpyeong Hospital, Seoul, Republic of Korea Background: The aim of this observational study was to determine whether subthreshold bipolarity affects treatment response and remission in patients with major depressive disorder receiving antidepressant (AD) monotherapy over a 6-month follow-up period. Methods: Seventy-eight patients with major depressive disorder were stratified into two subgroups according to the presence of subthreshold bipolarity, identified using the Korean version of the Mood Disorder Questionnaire (K-MDQ), which classifies patients as positive for a screening of bipolarity based on the cutoff for the total K-MDQ score (ie, 7 points). They received AD monotherapy such as escitalopram, sertraline, paroxetine, or tianeptine for 6 months. The Beck Depression Inventory (BDI), Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Scale, and Beck Scale for Suicide Ideation were applied at baseline, 1 week, 3 weeks, 2 months, 3 months, and 6 months. Results: The mean HAMD, BDI, and Beck Scale for Suicide Ideation scores were higher in the bipolarity group than in the nonbipolarity group at 3 weeks. The mean BDI score was also higher in the bipolarity group than in the nonbipolarity group at 6 months. Evaluation of the ratio of improvement for each scale revealed different patterns of percentage changes between the two groups over the 6-month follow-up period. Furthermore, the response and remission rates (as assessed using BDI and HAMD scores) were higher in the nonbipolarity group than in the bipolarity group, with the exception of HAMD scores at the 3-week follow-up time point. Conclusion: The findings of this study showed that depressed patients with bipolarity had a worse response to AD monotherapy than did those without bipolarity. Keywords: subthreshold bipolarity, antidepressant, major depressive disorder, treatment response, remission